The Impact of Learning Behavior and Student Engagement on Learning Outcomes in Geography Subjects at Junior School Level - Bintang Ibnu Yan Kanapi; Ratih Puspita Dewi; Sainee Tamphu (Universitas Negeri Gorontalo, 2024)
Geography is a science that deals with all activities and symptoms found on earth. At the junior high school level, geography is integrated into integrated social studies subjects. Geography is also an important social science to be implemented in lower secondary schools, but in its application there are also factors for its success, including learning behavior and student involvement. The objectives of this research are1) Analyzing the effect of learning behavior on student geography learning results, 2) Analyzing the effect of student engagement on geography learning results, and 3) Analyzing the effect of learning behavior and student engagement on geography learning outcomes. This research used quantitative method. The population in this study were students from grade 7 to grade 9 at SMP Negeri 2 Kemalang totaling 584 students. The sample in this study consisted of 237 students. SThe sampling was conducted using the stratified random sampling technique. Data were obtained using observation, documentation, and questiinnaires. The data analysis techniques used in this study include descriptive statistic, simple correlation tests, and multiple correlation analysis. The result shiwed that 1) students have a level of learning behavior in the high category, 2) student learning engagement in geography subjects categorized into high category, and 3) There is no significant influence of learning behavior and student engagement on geography learning success. It can be observed that the r value is smaller than the r tabke value 0.059 0.134) and the significance value is above 0,05 (0.416 0.05).